Slutningen af "Lidet om Jesu Kristi Åbenbaring" - Johansen, Steen (Grundtvig-studier, 1959)
The Concluding Section of “A Little About the Revelation of Jesus Christ. . . (“ Grundtvig-Studier”, 1956, P. 64- 75). Edited by Steen Johansen. In the very extensive Grundtvig Archives in the Royal Library in Copenhagen, a single manuscript of Grundtvig’s may often be divided into many parts, so that one has to search for the different sheets or pages in different places in the archives. In “ Grundtvig-Studier” for 1956 there was published a manuscript of his, the concluding section of which was missing. This concluding section has now been found and is published herewith. The manuscript dates from 1810, a year full of ferment and crisis in the life of the young Grundtvig. Through the study of history and reading the Bible he finds his way forward to his (first) Christian phase. In the light of the Revelation of St. John he seeks to understand his own period, and eloquently seeks to communicate to his countrymen his own faith and his enthusiasm for history and the achievements of their ancestors. That, very briefly, summarises the substance of the collected text, which is of considerable value for an understanding of the spiritual development of the young Grundtvig.